Peran Mediasi Digitalisasi Akuntansi Pada Hubungan Literasi Akuntansi Dan Kepatuhan Pajak UMKM di Kota Jambi - Erviando Z, Robby; Simanjuntak, Pranatalindo (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2025)
The development of digital technology requires Small and Medium Enterprises (SMEs) to improve their accounting skills and adopt digital-based recording systems to fulfill their tax obligations appropriately and accurately. This study aims to analyze the effect of accounting literacy on SME tax compliance in Jambi City and examine the mediating role of accounting digitalization in this relationship. The study used a quantitative approach with a survey method of 88 SMEs in Jambi City, and the data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results show that accounting literacy has a positive and significant effect on tax compliance, as well as a significant effect on accounting digitalization. Accounting digitalization has also been shown to have a positive effect on SME tax compliance. In addition, accounting digitalization acts as a mediator that strengthens the influence of accounting literacy on tax compliance, thus indicating that a good understanding of accounting will more optimally encourage tax compliance when supported by the use of digital accounting technology. These findings emphasize the importance of integrating accounting literacy capabilities with the adoption of accounting digitalization in improving the quality of SME tax reporting and compliance.